Epilithic diatoms (Bacillariophyceae) as indicators of water quality in the Upper Lerma River, Mexico - Garcia Segura, Virginia (2012)
The upper Lerma River is the most economically important basin of Mexico because it is the region where 80 % of the commercial activity of the country takes place, with 3500 industries, 750,000 Ha of irrigated land and 14 cities with populations over 100,000 inhabitants. Despite this relevance, little or no waste water treatment is done in the basin, which results in high contamination levels. The present paper deals with the taxonomy and ecology of epilithic diatoms collected at 11 sites in the basin in the dry and post-rainy seasons of the 2003-2005 period. This is the first study in an environmental direction of the diatoms of the upper Lerma River basin and the information generated will be used to propose, in the short-term, a Lerma River diatom index (IDL), supporting water quality monitoring programs. 178 taxa were recognized, of which 112 taxa (63%) were cosmopolitan or widely distributed. The genera with most species were Nitzschia (34), Navicula (19), Gomphonema (15), and Pinnularia (11). The dominant species in the studied locations and study period were Eolimna subminuscula (Manguin) Moser, Lange-Bertalot et Metzeltin, Gomphonema parvulum (Kützing) Kützing, Navicula veneta Kützing, Nitzschia capitellata Hustedt, N. sublinearis Hustedt, N. umbonata (Ehrenberg) Lange-Bertalot and Sellaphora pupula (Kützing) Mereschkowsky, which are characterized as tolerant to α-mesosaprobic to polysaprobic conditions, and to high nitrogen content. Trends in distribution of diatom species in the sampling sites were explained by variations in environmental parameters such as depth, conductivity, pH, temperature, and total dissolved solids.